Pengaruh Kualitas Kehidupan Kerja Terhadap Produktivitas Karyawan Produksi PT. Dharma Polimetal tbk. - Irham Habibi Fanindra; Yudi Tri Harsono (Flourishing Journal, 2022)
This study aims to determine the effect of quality of work life on the productivity of PT Dharma Polimetal Tbk production employees. The hypothesis of this study is that there is an effect of work life quality on the productivity of PT Dharma Polimetal Tbk production employees. The subjects of this study are 218 production employees of PT Dharma Polimetal Tbk. This research data collection technique uses a questionnaire consisting of a scale of quality of work life and production data of PT Dharma Polimetal Tbk. The Work Life Quality Scale consists of 35 items adapted from the Quality of Work Life scale compiled by Timossi, Pedroso, Francisco, and Pilatti (2008) based on Walton's theory (in Robbins, 2002) using Confirmatory Factor Analysis (CFA) to confirm whether indicator variables can be used to confirm a factor, the work life quality scale has an RMSEA value, CFI, and TLI that fit the criteria for obtaining a fit model. Analysis of research data for hypothesis testing using simple linear regression, the results showed a significant effect of quality of work life on productivity in PT Dharma Polimetal Tbk production employees with a significance value (p) of < 0.05 and an effective contribution of 12.8%.Abstrak Tujuan penelitian ini untuk mengetahui pengaruh kualitas kehidupan kerja terhadap produktivitas karyawan produksi PT Dharma Polimetal Tbk. Hipotesis penelitian ini adalah terdapat pengaruh kualitas kehidupan kerja terhadap produktivitas karyawan produksi PT Dharma Polimetal Tbk. Subjek penelitian ini adalah 218 karyawan produksi PT Dharma Polimetal Tbk. Data penelitian diambil melalui teknik kuesioner yang mencakup skala kualitas kehidupan kerja dan data produksi PT Dharma Polimetal Tbk. Skala Kualitas Kehidupan Kerja mencakup 35 butir item yang diadaptasi dari skala Quality of Work Life oleh Timossi, Pedroso, Francisco, dan Pilatti (2008) berdasarkan teori Walton (dalam Robbins, 2002) mempergunakan CFA (Confirmatory Factor Analysis) guna mengonfirmasi apakah variable-variabel indikator dapat digunakan untuk mengkonfirmasi sebuah factor, skala kualitas kehidupan kerja memiliki nilai RMSEA, CFI, dan TLI yang sesuai dengan kriteria untuk memperoleh model fit. Analisis regresi linier sederhana dimanfaatkan untuk uji hipotesis, dan didapatkan hasil adanya pengaruh signifikan kualitas kehidupan kerja terhadap produktivitas pada karyawan produksi PT Dharma Polimetal Tbk dengan nilai signifikansi (p < 0,05 serta sumbangan efektif sejumlah 12,8%.